182 Real world experience of pembrolizumab monotherapy in patients with recurrent or persistent cervical cancer: a Korean multi-center retrospective study(KGOG1041). (13th November 2020) - Choi, M; Kim, Y; Lee, J; Lee, Y
Abstract : Objectives: To investigate the antitumor activity and safety of pembrolizumab in patients with recurrent cervical cancer in real world practice. Methods: We conducted a multi-center retrospective study of patients with recurrent or persistent cervical cancer treated with pembrolizumab at a dose of 200 mg every 3 weeks at 16 institutions in Korea. The primary endpoint was the objective response rate and safety. Results: Data of 117 patients were treated with pembrolizumab between 2016 and 2020 was available. Median age was 53 years(range, 28–79 years). 64(54.7%) of patients had ECOG of performance status of ≥2. 49(41.9%) patients were FIGO stage ≥III at diagnosis. 88(75.2%) patients had histology of squamous cell carcinoma. The median number of prior chemotherapy lines was 2(range, 1–6). During the median follow-up of 4.9 months(range, 0.2–35.3), the objective response rate was 9.4% with 3 complete responses and 8 partial responses. Median time to response was 2.8 months(range 1.4–13.4). Median duration of response was not reached. In the population of patients with favorable performance status(ECOG ≤1)(n=53), the ORR was 18.9% and median time to response of them was 3.0 months(range, 1.4 to 13.4), median duration of response was 8.9 months(range, 7.3 to 10.4). Any adverse events occurred in 55(47.0%) of patients including 8(6.8%) patients who experienced grade ≥3 events. Two of them were suspicious treatment-related death. Conclusions: Pembrolizumab monotherapy demonstrated modest antitumor activity in patients with recurrent or persistent cervical cancer comparable as previously reported clinical trials, although in patients with favorable performance status showed effective antitumor activity. Some safety profiles should be carefully monitored.